“Bank titil” : The Benefits and How It is in Islamic Economic Perspectives - Happy Sista Devy; Rizky Amalia; Annisa Qurrota A'yun (Soegijapranata Catholic University, 2021)
The purpose of this research is to find how the superiority of the mobile bank or bank titil in the community and how it is viewed from an Islamic economic perspective. This research is a field research conducted using a qualitative approach. The snowball sampling technique was used to obtain the informants who use the services of a bank titil. Data from the key informants are then analyzed using three steps that occur simultaneously, namely data reduction, data presentation (display), and drawing conclusions/verification. The result of this research is that superiority of a mobile bank or bank titil in the community is related to the convenience in transaction provided by a mobile bank or bank titil. First, it is simple requirements. The second is fast disbursement. Third, there is no collateral or guarantee must be given to the titil bank as an official bank institutions are required. However, with the facilities provided by a mobile bank or bank titil, its practice basically contains harms which makes residents remain in a circle of poverty because of their dependence on the services of the mobile bank or bank titil.